Basic Psychological Needs, Burnout and Engagement in Sport: The Mediating Role of Motivation Regulation - De Francisco, Cristina (Int J Environ Res Public Health, 2020)
The purpose of the present research was to analyze the mediating role of motivational regulation between the satisfaction of basic psychological needs and burnout and engagement in athletes. From different sports 1011 young Spanish athletes participated in the study. Participants completed several measurement instruments concerning: the Basic Needs Satisfaction in Sport Scale, Behavioral Regulation in Sport Questionnaire, Athlete Burnout Questionnaire and Athlete Engagement Questionnaire. The results of structural equation modeling showed that the satisfaction of basic psychological needs has direct effects on burnout and engagement: a negative effect on athlete burnout (–0.49, p < 0.001) and a positive effect on engagement (0.54, p < 0.001). In addition, the satisfaction of basic psychological needs has a partial indirect effect over these variables in the same direction mediated by the self-determined degree of motivation. Thus, low levels of self-regulated motivation are positively related to burnout, but high levels of self-determined motivation are not. The same was observed with engagement, but vice versa: high levels of self-determined motivation are positively related to athlete engagement, but low levels of self-determined motivation are not. The proposed model explained 37% of the variance of burnout and 51% of the variance of engagement.